ANALISIS KETIDAKSTABILAN PARAMETRIK MEKANISME EMPAT BATANG ELASTIK - Huda, Syamsul; Mahyuddin, Andi Isra (Mesin, 2002)
The need to increase operational speed and reduce the inertia effects led to the design of slender members. Consequently, elasticity of these members could no longer be neglected. The elasticity results in varying stiffness of the elastic member leading to parametric excitation. The dynamic behavior of an elastic coupler of a four-bar mechanism is investigated. The governing equation is nonlinear, partial differential equation with time-varying parameters. Perturbation method is employed to linearize the equation and the dynamic response is obtained using a closed-form numerical solution algorithm constructed through the discretization of the parameters continua. The dynamic stability of the system is evaluated based upon Floquet Theory. The results are presented in the form of parametric stability charts, and the dynamic stability analysis results were validated by a direct-integration method. The response become unstable at several bands of frequency. The effects of external force, damping and ratio of follower-to-coupler mass were examined. Results show that increase in tensile force, damping, and the mass ratio increased the stability of the elastic coupler.